The role of neuroimaging in the determination of brain death - Corrêa,Diogo Goulart (2022)
Abstract Brain death is the irreversible cessation of all brain function. Although protocols for its determination vary among countries, the concept of brain death is widely accepted, despite ethical and religious issues. The pathophysiology of brain death is related to hypoxia and ischemia in the setting of extensive brain injury. It is also related to the effects of brain edema, which increases intracranial pressure, leading to cerebral circulatory arrest. Although the diagnosis of brain death is based on clinical parameters, the use of neuroimaging to demonstrate diffuse brain injury as the cause of coma prior to definitive clinical examination is a prerequisite. Brain computed tomography (CT) and magnetic resonance imaging (MRI) demonstrate diffuse edema, as well as ventricular and sulcal effacement, together with brain herniation. Angiography (by CT or MRI) demonstrates the absence of intracranial arterial and venous flow. In some countries, electroencephalography, cerebral digital subtraction angiography, transcranial Doppler ultrasound, or scintigraphy/single-photon emission CT are currently used for the definitive diagnosis of brain death. Although the definition of brain death relies on clinical features, radiologists could play an important role in the early recognition of global hypoxic–ischemic injury and the absence of cerebral vascular perfusion.